We know that
The Standard Form<span> of a </span>Quadratic Equation<span> is
</span> ax²<span> + bx + c = 0
</span>
then
for x=0 y=-6
a*0² + b*0 + c = -6---------> c=-6
for x=1 y=2
a*1² + b*1 -6 = 2---------> a+b=8---------> a=8-b---------> equation 1
for x=3 y=-0
a*3² + b*3 -6 = 0---------> 9a+3b=6---------> equation 2
<span>substituting 1 in 2
9*(8-b)+3b=6------> 72-9b+3b=6---------> 6b=66--------> b=11
a=8-11-------> a=-3
so
a=-3
b=11
c=-6
</span>Standard Form of a Quadratic Equation is
-3x² + 11x - 6 = 0
<span>
the answer is
</span> -3x² + 11x - 6 = 0<span>
</span>
Ta3 l3able fi bi idek l ndaf li ba3dak mghassalon
Answer: -1/2
Step-by-step explanation:
Slope is change in y over change in x. Y shifts down -1, while X shifts to the right 2
Answer:
1: 7x+19=40
2: 19+7x=40
Step-by-step explanation: